Cyclical Public Policy and Financial Factors - RANA, Vishrut Dhirendra (Institutional Knowledge at Singapore Management University, 2015)
The Great Recession of 2009 motivated a growing body of research on the quantitative modeling of financial factors and appropriate policy responses. This dissertation is a part of that line of research and looks at the quantitative macroeconomic effects of financial factors on business cycles. The dissertation uses quantitative macroeconomic general equilibrium models (popular dynamic stochastic general equilibrium (DSGE)) that allow flexibility in micro-founded modeling of macroeconomic environments. The dissertation captures financial factors through explicit modeling of financial intermediation, featuring costly state verification and collateral constraints as financial frictions. The first chapter offers a new quantitative model of credit cycles with endogenous leverage for financial intermediaries. Credit cycle dynamics emerge in a model with endogenous financial intermediary leverage and costly state verification. A trade-off between costly bank capital and a benefit of capital as a buffer against adverse shocks drives intermediary leverage. Bank capital functions as a buffer by reducing value-at-risk. Bank capital is costly as households require a premium to hold risky capital whereas deposits are insured. Changes in intermediary balance sheet size drive credit supply. The model displays three active credit channels: the business conditions channel, the bank net worth channel, and the funding cost channel. The model delivers empirically observed procyclical credit conditions. The second chapter investigates how bank monitoring dynamics evolve over the business cycle. The model features lognormal idiosyncratic productivity shocks for firms and endogenous default thresholds with costly state verification. The model presented in this chapter features financial intermediaries who engage in risk-shifting over the business cycle by reducing monitoring activity during business cycle upturns when the chances of loan losses are lower. Bank monitoring is costly, but it can indirectly reduce loan default probabilities by preventing firm moral hazard. As aggregate default probabilities fall over the business cycle, the marginal benefit of loan monitoring drops. In addition, intermediary monitoring is inefficiently low because firms holdup part of the benefit of monitoring. The third chapter abstracts from financial intermediation and looks at how tax policy should vary across the business cycle in the presence of financial frictions. Financial factors in the model give rise to heterogeneity among households. Optimal income tax rates are more volatile for lower income households. The paper looks at the quantitative properties of Ramsey optimal income tax rates as well as optimal public goods provision.